Head of School Strategy in Optimizing the Growth Mindset of Teachers to Realize the Vision of the Merdeka Curriculum - Ningtyas, Putri Vindhian; Zulkarnain, Wildan; Juharyanto, Juharyanto; Sultoni, Sultoni (Journal of Education for Sustainability and Diversity, 2025)
A growth attitude is crucial for any teacher, as it can serve as a motivating factor when confronted with changes in the curriculum. This research aims to identify the school principal's strategy for enhancing teachers' growth attitudes to accomplish the Merdeka curriculum vision at SD Anak Saleh Kota Malang. This study employs a qualitative methodology, specifically utilizing a case study design. Research indicates that teachers have a growth mindset, which is characterized by their willingness to embrace change, their commitment to self-improvement, their positive reactions to changes in the curriculum, and their dedication to lifelong learning. The principal strategy in optimizing the growth mindset of teachers as an effort to realize the vision of an independent curriculum at SD Anak Saleh Malang City, include holding weekly meetings, supporting teacher scientific upgrades, monitoring teacher performance consistently, and applying the principle of alignment. The indicators of the success of developing a teacher's growth mindset are teacher intention in teaching, high teacher responsibility, and a pleasant learning atmosphere.